Author Identification of Bengali Poems - Pandian, A.; Manikandan, K.; Ramalingam, V.; Bhowmick, Payal; Vaishnavi, Sree (International Journal of Engineering and Technology, 2018)
Author identification of Bengali poems is a project mainly focusing on identification of an author of a poem. We train the system using a dataset consisting of features extracted from poems by various authors. Features like count of characters, words, spaces, vowels and consonants of Bengali poems are considered. The training algorithm used is J48 decision tree. It has additional features of J48 like it accounts for missing values, prunes decision trees, and derives rules from the data, etc. All of this is helpful when we want to classify with larger datasets. Â